Endothelial Hyper-Permeability Induced by T1D Sera Can be Reversed by iNOS Inactivation - Cazzaniga, Alessandra (Int J Mol Sci, 2020)
Type 1 Diabetes Mellitus (T1D) is associated with accelerated atherosclerosis that is responsible for high morbidity and mortality. Endothelial hyperpermeability, a feature of endothelial dysfunction, is an early step of atherogenesis since it favours intimal lipid uptake. Therefore, we tested endothelial leakage by loading the sera from T1D patients onto cultured human endothelial cells and found it increased by hyperglycaemic sera. These results were phenocopied in endothelial cells cultured in a medium containing high concentrations of glucose, which activates inducible nitric oxide synthase with a consequent increase of nitric oxide. Inhibition of the enzyme prevented high glucose-induced hyperpermeability, thus pointing to nitric oxide as the mediator involved in altering the endothelial barrier function. Since nitric oxide is much higher in sera from hyperglycaemic than normoglycaemic T1D patients, and the inhibition of inducible nitric oxide synthase prevents sera-dependent increased endothelial permeability, this enzyme might represent a promising biochemical marker to be monitored in T1D patients to predict alterations of the vascular wall, eventually promoting intimal lipid accumulation.